N. Machiavelli and Machiavellianism - Mažeikis, Gintautas (Politologija, 1999)
In the article the following problems are analysed: the problem of the relationship between the political philosophy of a widely-known philosopher of the Renaissance period Niccolo Machiavelli, on the one side, and Machiavellianism - on the other; the origins of the conception of Machiavellianism, how it came about; and the last - both political and sociological biases of Machiavellianism. There is no doubt, according to the author, that Machiavelli's ideas were to a very large extent influenced by anthropocentrical Weltanschauung of the Renaissance. Herein the human being was viewed and described as a microcosmos, and the new formula of individual were searched for. The microcosmos was but a magical cosmic category that came to be explained by such notions as fortuna and virtù. Furthermore, the quest was influenced by such forces as the intellectual movements of studia humanitatis and studia civitatis, plus the magic-aesthetic discourses of thought.Machiavelli's idea of a political body, that developed in his masterpieces - The Prince and The Discourses - was expanded and cultivated in a historico-cosmic context of the same reality - the Renaissance. Author notes that Machiavellianism is quite different from Machiavelli's philosophical ideas and, when viewed, Machiavelli himself should not be identified with Machiavellianism. It was formed by such Protestant and antimachiavellian discourses (latter characteristic to the period of Counter-Reformation) the epistemological fundamentals of which belonged to the New Ages, its disciple - the science, where the abstract idea of Descartes' cogito came as a substitute for Renaissance's microcosmos (This is exactly what the author sets as a thesis for the discussion in this article.) The latter ideas and trends came to serve as a basis for the rehabilitation of Machiavellianism in the classical philosophy of Germany in the XIX century and in the totalitarian ideologies of XX century. Political amorality and scientific instrumentalism have shaped the sociological principles for the analysis of Machiavellianism. On the other hand, the XXth-century hermeneutics has provided the means for the reconstruction of non-Machiavellistic picture of Niccolo Machiavelli.In the first section of the article the author debates the nature of Machiavellianism and elucidates three standpoints regarding it. He writes that all of them are closely connected, and these are: Protestant intellectual antimachiavellianism, Counterreformationary critics of the abstraction from religious morality and, third, the New Ages' abstracted interpretations of Niccolo Machiavelli's The Prince (originally written in 1513). The magnitude and diversity of ideas, antimachiavellianism, Machiavellianism and Counterreformation, is illustrated in subsequent paragraphs and sections.It said that, although at first Machiavelli and his ideas were tolerated by the Popes, later the works were banned and included into the Index. Why? The answer is: if the Protestant theologicians and politics viewed Machiavelli as primarily a Catholic politician, the leaders of the Counter-Reformation did so from the standpoint that he is the demolisher of religious morality and a secular thinker. Author writes that this is natural. These thoughts incited the birth of antimachiavellian works later reinforcing additional trends of antimachiavellianism. In this article the author reviews how in different historic periods the ideas of Niccolo Machiavelli were viewed and treated, and later transformed into Machiavellianism, for example, the classical philosophy of Germany in the XIX century, XXth-century hermeneutics, etc. Throughout the article the author oftentimes refers to different philosophers of XVIII, XIX and XX centuries, as well as to the works of the scientists of philosophy, Sabine and Thorson, Henning and Six, Parel and Schnapp, Berlin and Cassirer, Skinner and Lerner. The manner is descriptive, however, the conclusions appear interesting and original (for example, thoughts on the relationships between the ideas of Machiavelli and Machiavellianism with Napoleon).In the second section of the work the relationship between the political philosophy of a widely-known philosopher of the Renaissance period Niccolo Machiavelli, on the one side, and Machiavellianism - on the other is analysed. It is said, that Machiavelli's philosophy is oftentimes discussed in two ways: as a radical version of studia civitatis (civil humanism) and, second, as one of the first instrumental political, or politico-philosophical, theories of Renaissance, where the conception of a new state - stato - was moulded; idea of a cosmic and civil rational valour - virtù, etc.In the third section, an idea of a Machiavellist as a specific type of a politician is revealed, in the fourth part - sociological pattern of Machiavellianism discussed. It is said that Machiavellianism is not but a blind implementation of one's ends with brutal power. For Machiavellianism, the morality of means or ends is not as important as their efficiency. The good and the kindness here remains but as one of many instruments, equal to a murder or bribery. On the other hand, antimachiavellianism accentuate the opposite features - the good, generosity, etc., which all have their sociopsychological effects.Both forces were influential, and it is said that not only the ideas and treatments of Machiavellianism and antimachiavellianism be separated, but, likewise noted, that Machiavellianism is quite different from Machiavelli's philosophical ideas and, when viewed, Machiavelli himself should not be identified with Machiavellianism. It was formed by such Protestant and antimachiavellian discourses (latter characteristic to the period of Counter-Reformation) the epistemological fundamentals of which belonged to the New Ages, its disciple - the science.
Keywords: -